Secondary Protein Aggregates in Neurodegenerative Diseases: Almost the Rule Rather than the Exception - Fabio Moda; Arianna Ciullini; Ilaria Linda Dellarole; Annalisa Lombardo; Nicole Campanella; Giuseppe Bufano; Federico Angelo Cazzaniga; Giorgio Giaccone (Frontiers in Bioscience-Landmark, 2023)
The presence of protein aggregates is a hallmark of many neurodegenerative diseases, including Parkinson’s disease (PD), Alzheimer’s disease (AD), and frontotemporal lobar degeneration (FTLD). Traditionally, each disease has been associated with the aggregation of specific proteins, which serve as disease-specific biomarkers. For example, aggregates of α-synuclein (α-syn) are found in α-synucleinopathies such as PD, dementia with Lewy bodies (DLB), and multiple system atrophy (MSA). Similarly, AD is characterized by aggregates of amyloid-beta (Aβ) and tau proteins. However, it has been observed that these protein aggregates can also occur in other neurodegenerative diseases, contributing to disease progression. For instance, α-syn aggregates have been detected in AD, Down syndrome, Huntington’s disease, prion diseases, and various forms of FTLD. Similarly, Aβ aggregates have been found in conditions like DLB and PD. Tau aggregates, in addition to being present in primary tauopathies, have been identified in prion diseases, α-synucleinopathies, and cognitively healthy aged subjects. Finally, aggregates of TDP-43, typically associated with FTLD and amyotrophic lateral sclerosis (ALS), have been observed in AD, progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), MSA, DLB, and other neurodegenerative diseases. These findings highlight the complexity of protein aggregation in neurodegeneration and suggest potential interactions and common mechanisms underlying different diseases. A deeper understating of this complex scenario may eventually lead to the identification of a better elucidation of the pathogenetic mechanisms of these devastating conditions and hopefully new therapeutic stragegies.